The influence of social support on sexual mental health of female college students. Issue 28 (July 2018) - Wang, Yu-Hang; Shi, Zhou-Ting
Abstract : Abstract: The aim of this study was to explore the impact of social support on female college students' sexual mental health (SMH) on the basis of realizing the current status of their SMH. A total of 627 female college students from 5 colleges and universities in Hangzhou were enrolled in the study and provided with questionnaires to evaluate their SMH and social support rating scale. The scores of SMH and social support were 2.46 ± 0.29 and 38.29 ± 4.37, respectively. The scores of SMH of female college students in different grades and places of origin were significantly different ( P < .05). There was a negative correlation between the scores of each dimension of SMH and that of social support ( r = −0.157 to −0.419, P < .01). Social support has an important influence on the SMH of female college students. Higher level of SMH is associated with greater social support. Colleges and universities can improve the social support system of female students through various measures to improve their SMH.